Sweetpotato Whitefly B Biotype of Silverleaf Whitefly, Bemisia tabaci (Gennadius) or Bemisia argentifolii Bellows & Perring (Insecta: Homoptera: Aleyrodidae) - Heather J. McAuslane (EDIS)
This document is EENY-129, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2000. Revised: November 2002.